East Newton Street, n.d. - Unknown (Tufts Archival Research Center, 2005)
Street level view looking southeast from Washington Street to East Newton Street. The structures, which face Franklin Square, are (from left to right) the St. James Hotel, the New England Conservatory of Music and the Franklin House. Figures are seen on the sidewalks as well as one horse-drawn vehicle. 7 9/16 x 13 Photographs